Optimization of antioxidants with different fermentation time in the salvage industry infertile eggs - Fastawa Rajma; N. Nahariah; Fatma Maruddin (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
The eggs infertile is one alternative food to meet the nutritional needs and other benefts of eggs. The study aims to determine the effect of different fermentation time of the optimization efforts antioxidants in infertile eggs hatching the remaining results. The study design used a completely randomized design (CRD) with three treatments and fve replications. Study treatment was 0, 2 and 4 days. Materials used are infertile eggs hatching period of 18 days as many as 45 items. The parameters measured were the antioxidant activity, the concentration of antioxidants and thiobarbituric acid (TBA) and fat content. The results showed that the antioxidant activity in the rest of the infertile eggs hatching industry results highly signifcant effect increases with the length of fermentation consecutive 0 days amounted to 87.44%, amounting to 96.75% 2 days and 4 days amounted to 99.38%. The concentration of antioxidants in infertile eggs hatching salvage industry very signifcantly decreased with increasing fermentation time consecutive 0 days of 11.56%, 2 days of 10.66% and 4 days of 11.11%. TBA value (malonaldehid mg/10 mg) in infertile eggs hatching salvage industry very signifcantly decreased with increasing fermentation time consecutive 0 days of 0,09, 2 days of 0.08 and 4 days of 0.05. The percentage of fat in infertile eggs hatching salvage industry very signifcantly decreases with increasing length of fermentation consecutive days 0 of 11.56%, 2 days of 10.66% and 4 days of 11.11%. Fermentation for 2 days to optimize the rest of antioxidants in the eggs infertile hatching results.